2015
DOI: 10.1038/aps.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

Policresulen, a novel NS2B/NS3 protease inhibitor, effectively inhibits the replication of DENV2 virus in BHK-21 cells

Abstract: Aim: Dengue is a severe epidemic disease caused by dengue virus (DENV) infection, for which no effective treatment is available. The protease complex, consisting of nonstructural protein 3 (NS3) and its cofactor NS2B, plays a pivotal role in the replication of DENV, thus may be a potential target for anti-DENV drugs. Here, we report a novel inhibitor of DENV2 NS2B/NS3 protease and its antiviral action. Methods: An enzymatic inhibition assay was used for screening DENV2 NS2B/NS3 inhibitors. Cytotoxicity to BHK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Hence, to overcome such situation presently, available more resources, much faster, and advance scientific techniques need to be adopted and explored. Earlier, a number of studies have proposed various traditional and specific methods for the identification of different chemical entities and demonstrated their selective inhibition mechanism and inhibitory efficacy against NS3‐NS2B protease complex at different levels …”
Section: Introductionmentioning
confidence: 99%
“…Hence, to overcome such situation presently, available more resources, much faster, and advance scientific techniques need to be adopted and explored. Earlier, a number of studies have proposed various traditional and specific methods for the identification of different chemical entities and demonstrated their selective inhibition mechanism and inhibitory efficacy against NS3‐NS2B protease complex at different levels …”
Section: Introductionmentioning
confidence: 99%
“…Dengue is a virus that belongs to the genus Flavivirus, which has five known serotypes [ 4 ]. Dengue virus (DENV) co-circulates as a complex of five closely related but antigenically distinct serotypes (DENV-1 and DENV-5) [ 5 ], all of which are etiologic agents of dengue fever, life-threatening dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS) [ 6 ]. DENV-2 and DENV-3 have historically been the most prevalent agents that have caused severe disease [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shionogi Co., Ltd. performed the structure-activity relationship (SAR) studies of Xu's compound 9 (renamed as 1 43) ). After conducting alanine scanning on every residue in 1, they found that P1-3 strongly affected NS3/2Bpro activity.…”
Section: Non-linear Peptide Ns3/2b Protease Inhibitorsmentioning
confidence: 99%